Undisguised Kilings: Public Executions in China (United States, 1996)
This report, which accompanies the video "Undisguised Killing", has been issued to draw attention to the common practice of public executions in China. The absence of due process, an independent judicial system and the rule of law generally in China is not addressed here. The Laogai Research Foundation maintains that executions as a form of political education are a gross violation of basic human rights. In September 1983, Harry Wu, Executive Director of the Laogai Research Foundation, witnessed the public execution of forty-five prisoners in Zhengshou city in Henan. Prisoners were paraded through the streets, past crowds who lined both sides of the road to the execution site. Guards acted in perfect unison and followed the letter of some internal order for carrying out executions. As many as 100,000 people watched as forty-five guards carried out the final order. Days later, the courts posted the "criminal backgrounds" of each executed prisoner that justified the death penalty. The communist authorities in China have always believed that public executions intimidates the common citizen into submission and consolidate the perception of a strong government. Under this belief, party policy dictated that prisoners be paraded through the streets following sentencing and executions be publicized and attended by the populace. Following an expose into public executions in China by Newsweek magazine in 1984, the central government rethought its policy. The authorities issued new orders regarding executions, meant to cleanse the Party's reputation abroad by curbing the minitoring, photographing and other kinds of external coverage of the executions.